Tinjauan Hukum Islam terhadap Akad Jual Beli Menggunakan Kreweng : (Studi di Minggon Jatinan Hutan Kota Rajawali Batang) - Afifah, Nur; Khasanah, Uswatun; Novanta, Nabella Maharani (el hisbah Journal of Islamic Economic Law, 2021)
This journal examines the implementation of contracts used in buying and selling using kreweng money in Minggon Jatinan, the urban forest of Rajawali Batang, Central Java. This study aimed to analyze the consumer's muamalah by exchanging kreweng money and between consumers and food sellers. In addition, this research also provides an overview of the right way to make transactions at tourist attractions. As well as explaining the law of transactions using kreweng in buying and selling food. The research method used in this study is a field research method with descriptive analysis, namely the discussion obtained by collecting data from interviews and library sources about buying and selling contracts which are then compared with the maslahah theory. From the results of this study, the authors describe that there are two contracts in the transaction in minggon jatinan, in this buying and selling transaction, consumers use kreweng money as a medium of exchange. Kreweng money when converted to rupiah has a value of Rp. 2,000.00. The way to get it is by exchanging rupiah with kreweng money that the officer has provided on the spot.